Owady minujące liście dębu szypułkowego Quercus robur L. w Bydgoszczy i okolicach - Wrzesińska, Danuta (Leśne Prace Badawcze, 2017)
This research on the occurrence of insects mining leaves of the English oak Quercus robur was performed between 2011–2012 in Bydgoszcz and in nine neighbouring sites: seven in forest areas and two in an urbanized environment. The analysis of the gathered material revealed the occurrence of insects from three different orders, Coleoptera, Hymenoptera and Lepidoptera, and 10 families: Curculionidae, Tenthredinidae, Bucculatricidae, Coleophoridae, Eriocraniidae, Gracillariidae, Heliozelidae, Incurvariidae, Nepticulidae and Tischeriidae. In total, 21 insect species were collected from Q. robur ; most of them at forest sites. A slightly lower number of species was recorded at Janowo, where oaks were growing on the edge of the forest in the vicinity of a transport route with heavy traffic. Even fewer taxa were observed in the vicinity of urbanised areas; in the city park on the Bydgoszcz Canal and in Fordon . The most abundant species on the English oak were Tischeria ekebladella (Bjerk.) and Phyllonorycter heegeriella (Zell.).